Local Language Revitalization Strategies as Pathways to Child Participation: A Nonformal Perspective in Child-Friendly Villages - Kusumawardani, Erma; Septiarti, Serafin Wisni; Sugito, Sugito; Setiana, Dafid Slamet (International Journal of Language Education, 2025)
This research aims to explore local language revitalization strategies as a pathway to children's participation within the Child-Friendly Village framework from a non-formal education perspective. Using a qualitative approach with the Participatory Rural Appraisal (PRA) method, this research involved 17 participants consisting of volunteers, community leaders, and parents, with data collection through focus group discussions, participatory mapping, and observation. The research results show that the local language revitalization strategy is implemented through participatory learning, the use of local languages in social spaces such as mosques and community activity centers, and children's activities based on outbound activities. As a result of this strategy, social identity is strengthened, communication accessibility is increased, and children's involvement in village decision-making is encouraged. However, challenges such as language shift, social stigma, and media limitations persist. In effect, this research confirms that integrating local language revitalization into non-formal education practices and village policies can be an important means of strengthening children's participation while maintaining the sustainability of local culture.